Patuas and Patua art in Bengal - McCutchion, David J.; Bhoumik, Suhrid K. (Calcutta : Firma KLM, 1999)
Study on folk painting and folk poetry of Juang, Indic people of West Bengal.
Keywords: Folk songs, Bengali -- India -- West Bengal -- Texts; Folk poetry, Bengali -- India -- West Bengal -- Translations into English; Painting, Bengali -- India -- West Bengal; Folk art -- India -- West Bengal; Juang (Indic people) -- India -- West Bengal